The ERI-6/7 helicase acts at the first stage of an siRNA amplification pathway that targets recent gene duplications. - Sylvia E J Fischer; Taiowa A Montgomery; Chi Zhang; Noah Fahlgren; Peter C Breen; Alexia Hwang; Christopher M Sullivan; James C Carrington; Gary Ruvkun (PLoS Genetics, 2011)
Endogenous small interfering RNAs (siRNAs) are a class of naturally occuring regulatory RNAs found in fungi, plants, and animals. Some endogenous siRNAs are required to silence transposons or function in chromosome segregation; however, the specific roles of most endogenous siRNAs are unclear. The helicase gene eri-6/7 was identified in the nematode Caenorhabditis elegans by the enhanced response to exogenous double-stranded RNAs (dsRNAs) of the null mutant. eri-6/7 encodes a helicase homologous to small RNA factors Armitage in Drosophila, SDE3 in Arabidopsis, and Mov10 in humans. Here we show that eri-6/7 mutations cause the loss of 26-nucleotide (nt) endogenous siRNAs derived from genes and pseudogenes in oocytes and embryos, as well as deficiencies in somatic 22-nucleotide secondary siRNAs corresponding to the same loci. About 80 genes are eri-6/7 targets that generate the embryonic endogenous siRNAs that silence the corresponding mRNAs. These 80 genes share extensive nucleotide sequence homology and are poorly conserved, suggesting a role for these endogenous siRNAs in silencing of and thereby directing the fate of recently acquired, duplicated genes. Unlike most endogenous siRNAs in C. elegans, eri-6/7-dependent siRNAs require Dicer. We identify that the eri-6/7-dependent siRNAs have a passenger strand that is ∼19 nt and is inset by ∼3-4 nts from both ends of the 26 nt guide siRNA, suggesting non-canonical Dicer processing. Mutations in the Argonaute ERGO-1, which associates with eri-6/7-dependent 26 nt siRNAs, cause passenger strand stabilization, indicating that ERGO-1 is required to separate the siRNA duplex, presumably through endonucleolytic cleavage of the passenger strand. Thus, like several other siRNA-associated Argonautes with a conserved RNaseH motif, ERGO-1 appears to be required for siRNA maturation.